Na delu, doma - Hočevar, Marjan (Teorija in praksa, 2021)
In the article, we conceptually discuss changes to how the spheres of life at home (living) and work (workplace) are organised concerning everyday practices in a time-space perspective. We start with the classical sociological dilemma about the mechanisms of differentiation and integration. The main research question is whether the Covid-19 pandemic, with its potentiated technological mediation, is accelerating the process of dedifferentiation of the spheres of home and work. We establish contradictory effects of this process, especially the problem of establishing privacy at home as a core for all activities. The manifestation of being tied to the home is domocentrism, which we associate with traditional, pre-industrial forms of the socio-spatial integration of homogeneous, undifferentiated spheres of life. These potentially more permanent shifts are explained as regressive.
Keywords: Covid-19; dediferenciacija; Delo na domu; dom/delo; Epidemics; Epidemije; Home labor; prostor/čas; življenjske sfere